Rule of Law and Democratic Decline During States of Emergency – The Case of the Czech Republic - Jana Janderová (Central European Public Administration Review)
Purpose: This paper analyses the impact of the state of emergency declared during the Covid-19 pandemic on public administration, specifically focusing on the Czech Republic. It aims to understand the correlation between the rule of law, the legitimacy of measures taken during the pandemic, and the public’s willingness to comply with these measures. Design/Methodology/Approach: The paper employs a comparative study design, examining the consistency of pandemic measures with the core principles of the rule of law – legality, proportionality, and legitimate expectations. The study focuses on measures that restrict rights (e.g., right to education) and those that, conversely, grant rights (e.g., decisions on compensation bonuses). The methodology involves an analysis of the relevant case law, administrative practice, and data from several databases. Findings: The study reveals frequent breaches of legality and proportionality, both in the restriction and granting of rights. Findings indicate that the public’s willingness to comply with measures decreased when these were perceived as illegitimate. This was evident in the Czech Republic where, despite the persistence of most measures, the situation worsened during the autumn 2020 and spring 2021 waves of the pandemic. Practical Implications: The findings of this study have significant implications for public administration and policymaking, especially during times of crisis and declared state of emergency. The results highlight the importance of maintaining the rule of law and ensuring the legitimacy of public compliance measures. The study suggests that disregard for these principles can lead to a decline in public trust and cooperation, exacerbating the crisis. Originality/Value: This paper provides a unique perspective on the management of the Covid-19 pandemic, linking the rule of law with public compliance. It offers valuable insights for governments and policymakers on the importance of maintaining legality and proportionality in their measures, and the potential consequences of their disregard. What sets this study apart is its comprehensive analysis of both cases where rights were reduced (such as limitations of the right to education) and cases where rights were provided (such as the granting of compensation bonuses). This dual-focused approach offers a more holistic view of the impact of governmental measures during the pandemic. The study’s findings contribute to the broader understanding of crisis management and the role of public administration. This comprehensive approach enhances the originality and value of the research, making it a significant contribution to the field.